Tecnologia social para reciclagem do papel sulfite impresso - Fonseca, Carlos Oreques (2020)
The solid waste management process in Brazil represents an old problem, and it has been showing little evolution, even with federal and municipal laws that determine the procedures to be adopted. Allied to this, public and private companies are in the digital age, where administrative processes have migrated from paper to electronic media, leaving many confidential documents with no validity in their "archives". Printed sulfite paper is a waste widely found in garbage in Brazil, and it is the versatile and most used materials in our daily lives; however, we rarely think of new ways to reuse it and what the different risks are if it is improperly discarded. In this context, there is a need for studies that enable new alternatives and solutions for sustainable recycling of this type of material and, preferably, that this return does not cause negative impacts on the environment. The object of this research was the development of a sustainable technology, through experimental practices and analyzes, based on the composting process, as an alternative for use and disposal of the printed sulfite paper discarded in public and private institutions of Boa Vista / RR. Four experiments named E1, E2, E3 and E4 were set up, using different amounts of printed sulfite paper and one more pattern or a witness, called EP. The experimental process was carried out in industrial dumps, which are 80 cm high and have a capacity of 50 liters. In all experimental samples, sulfite paper was used, and the amount of paper inserted in the composters was on an increasing scale of 7.5%, 10%, 12.5% and 15% of total carbon material. The composting process took 150 days to present the final maturation characteristics, and the obtained results in all performed analyzes on the products originated from the experiments are considered satisfactory, as they are presented in accordance with the EP product -the witnessand current egislation. Thus, from the procedures carried out experimentally, E4 was selected, which had the largest amount of sulfite paper mass to indicate it as an efficient Sustainable Technology model in the recycling of printed sulfite paper, through an aerobic composting process in an informative and guiding booklet intended to be distributed mainly in public and private institutions. In the E4 experiment, unprecedented results were seen, such as the maximum amount of bond paper needed to get an organic product, rich in minerals and inside the average time stipulated by the literature for this process. It is a natural fertilizer of good quality, obtained with the use of easily accessible and low cost materials and equipment when verifying the risk and effectiveness of the technology in comparison with chemicals with the same objective. In this context, it is possible to conclude that the developed technology is sustainable and without negative impacts on the environment, being timely distributed to the target audience, since it offers, at the same time, a pre-technological asset (Technical-scientific methodology) and technological asset (product).